Participatory irrigation management (PIM) in Turkey: a case study in the Lower Seyhan Irrigation Project - Yazar A. (Water valuation and cost recovery mechanisms in the developing countries of the Mediterranean region, 2002)
The study analyzes the impact of management turnover on irrigation management and irrigated agriculture in selected irrigation associations in the Lower Seyhan Irrigation Project in Adana, Turkey.
Seminar: Water Valuation and Cost Recovery Mechanisms in the Developing Countries of the Mediterranean Region; 2002/06/15/17; Agadir (Morocco)